1124 Is Delayed Presentation A Prognostic Factor for The Survival of Patients with Esophageal Atresia More Than Associated Anomalies? Comparison Between Different Social Realities. (12th October 2021) - Arora, A; Raffaele, A; Agarwala, S; Parigi, G B; Manzoni, F; Klersy, C; Bhatnagar, V
Abstract: Background: The aim is to evaluate if different social reality could represent a prognostic factor as associated anomalies affecting survival of neonates with esophageal atresia (EA). Method: Retrospective analysis of records of neonates with EA with or without Tracheoesophageal Fistula (TEF) from January 2011 to September 2018 at Policlinico San Matteo Pavia, Italy(SMAT) and the All India Institute of Medical Sciences New Delhi, India (AIIMS).Survival was correlated with the presence of anomalies, different types and the number of organ systems involved.Age at presentation and birth weight were considered to find an association with mortality. Results: Out of 180 patients, 162 were from AIIMS and 18 from SMAT.The overall mortality was 28.85%, which occurred at AIIMS, being 0% at SMAT.83.33% at SMAT and 72.84% at AIIMS had associated anomalies.The mortality was 25% for neonates without an anomaly, being 26.15% for those with one (p > 0.05).No statistically significant correlation between outcome and associated anomalies was found.Instead, survival declines gradually as the age at presentation increases. Conclusions: The presence of associated anomalies paradoxically does not affect the outcome because incidence of delayed presentation has a stronger effect than the presence of associated anomalies. Sensibilization is necessary to improve survival in EA neonates in developing countries, such as India.